THE ORAL TRADITION OF PEOPLE'S BELIEFS ON THE PROHIBITING EXPRESSION OF THE BAKUMPAI SOCIETY OF THE BARITO REGION (TRADISI LISAN KEPERCAYAAN RAKYAT UNGKAPAN LARANGAN MASYARAKAT BAKUMPAI WILAYAH BARITO) - Rusma Noortyani; Jumadi Jumadi; Maryaeni Maryaeni; Fatchul Mu’in (Jurnal Gramatika, 2023)
The study's findings include: (1) the importance of the Bakumpai tradition in the Marabahan region, which possesses knowledge of nature, the paranormal, and causal relationships; and (2) the importance of the Bakumpai tradition in the Marabahan region in terms of educating and passing on the values of life to the next generation. In the Bakumpai community in the Marabahan region, this study intends to describe local wisdom in the oral tradition of traditional beliefs to prevent pregnancy, infancy, and childhood. This study is qualitative. Descriptive analysis is the technique employed. The Bakumpai neighborhood in the Marabahan region is the data source. The study's primary data sources are the oral traditions, words, and sentences of the Bakumpai community in the Marabahan region. The study's findings include the following: (1) the importance of the Bakumpai tradition in the Marabahan region, which has knowledge of nature, the paranormal, and causal relationships; (2) the importance of the Bakumpai tradition in the Marabahan region in terms of educating and instilling the values of life in the next generation with an exemplary approach; and (3) the importance of the Bakumpai tradition in the Marabahan region, which strengthens the family unit.